2019
DOI: 10.3390/s19091988
|View full text |Cite
|
Sign up to set email alerts
|

UP-Fall Detection Dataset: A Multimodal Approach

Abstract: Falls, especially in elderly persons, are an important health problem worldwide. Reliable fall detection systems can mitigate negative consequences of falls. Among the important challenges and issues reported in literature is the difficulty of fair comparison between fall detection systems and machine learning techniques for detection. In this paper, we present UP-Fall Detection Dataset. The dataset comprises raw and feature sets retrieved from 17 healthy young individuals without any impairment that performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
157
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(194 citation statements)
references
References 42 publications
(66 reference statements)
0
157
0
Order By: Relevance
“…Unlike other works in which falls were performed at the same place of the experimental scene [18,[22][23][24], in the present work we try to solve a more challenging task, namely to detect falls performed at different positions. To do so, the volunteer was asked to enter the room and imitate falling or normal daily activity while reaching one of four points (points 1-4 in Figure 4), thus the range between the subject and the radars varied from 1.0 to 2.0 m, moreover, for points 3 and 4 in Figure 4, the volunteer was only partially observed by bioradar No.…”
Section: Description Of the Experimental Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike other works in which falls were performed at the same place of the experimental scene [18,[22][23][24], in the present work we try to solve a more challenging task, namely to detect falls performed at different positions. To do so, the volunteer was asked to enter the room and imitate falling or normal daily activity while reaching one of four points (points 1-4 in Figure 4), thus the range between the subject and the radars varied from 1.0 to 2.0 m, moreover, for points 3 and 4 in Figure 4, the volunteer was only partially observed by bioradar No.…”
Section: Description Of the Experimental Proceduresmentioning
confidence: 99%
“…In most papers dealing with fall detection problem, it is proposed to select features from the raw data, construct a feature vector with a feature extraction technique, and use this vector for training a classifier [18,22,24]. Feature selection and extraction are methods used to convert the raw data into a low-dimensional subspace that contains all relevant information for a further classification step [33].…”
Section: Learning and Inferencementioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, contemporary research in the field of fall detection and verification of the elderly and impaired population is extensive. Among the critical challenges and issues reported in the literature is the difficulty of an accurate comparison between fall detection systems and machine learning techniques for detection [12].…”
Section: Introductionmentioning
confidence: 99%
“…In response to a few multimodal datasets developed upon different human activities, including publicly available falls, Martinez-Villasenor et al presented the UP-Fall Detection Dataset. The authors decided to choose a 10-fold configuration based on relevant research and everyday practices reported in machine learning [12]. The dataset was adaptable enough to summarize full information from wearable sensors, ambient sensors, and vision devices.…”
Section: Introductionmentioning
confidence: 99%